Sequential Suture Passage With Delayed Tying for Capsular Closure in Hip Arthroscopy - Logan Mays, B.A.; Joseph Anderson, M.D.; Caleb J. Bischoff, D.O.; Te-Feng Arthur Chou, M.D.; Steven F. DeFroda, M.D., M.Eng. (Arthroscopy Techniques)
Recent advancements in hip arthroscopy highlight the importance of capsular closure for managing femoroacetabular impingement and instability. This study introduces a modified technique using delayed suture tying to optimize visualization and precision. By placing all sutures before tying, the method preserves an unobstructed view, minimizes entanglement, and ensures accurate closure. Beneficial for interportal and T-capsulotomy closure, it reduces technical difficulty, improves efficiency, and enhances outcomes. Delayed suture tying optimizes capsular repair making hip arthroscopy more reproducible and effective while improving patient outcomes.